Le changement des conceptions des étudiants de sciences du collégial à l'égard de la structure de l'atome en lien avec les pratiques enseignantes : une analyse qualitative - CHRISTINE MARQUIS; BRUNO POELLHUBER (Metaichmio Publications, 2023)
This paper aims to describe and explain the impact of certain teaching practices on collegen students' conception changes. Teachers' practices during a lesson on atomic models were studied, as well as students' conceptions, based on diagrams they drew and commented, before and after the lesson. Aware of the difficulty of changing these students' conceptions, teachers deliberately use certain forms of content representations as well teaching activities designed to change them. The students' conceptions generally evolve towards a more advanced level of formulation corresponding to the probabilistic model, even if several errors still remain.